Hakikat Pendidikan Islam - Ujang Sayuti; Al Ikhlas; Andi Fery; Zulmuqim Zulmuqim; M. Zalnur (Journal on Education, 2022)
Education is a conscious and deliberate effort. Education embodies the learning process so that learners are actively developing their potential to have the spiritual power of religion, self-control, personality, intelligence, noble character, as well as the necessary skills themselves, society, nation and state. Education is defined as the reciprocal of each person in coping with nature, with friends, and with the universe. Education is also an organized and complete development of all human potential; moral, intellectual and physical, and the individual personality and society are expected usefulness in order to collect all of these activities for the purpose of his life (the final destination). The explanation above clarifies that education is a process or a conscious effort to provide guidance or direction to the development of children’s physical and spiritual sense of humanity towards perfection. In other words, the essence of education is the formation of a mature man, having skill, impeccable craftsmanship with major personality or character. This article elaborates the nature of education in the context of the macro.